Second Language Use Facilitates Implicit Emotion Regulation via Content Labeling - Morawetz, Carmen; Oganian, Yulia; Schlickeiser, Ulrike; Jacobs, Arthur M.; Heekeren, Hauke R. (Frontiers in Psychology, 2017)
Previous studies reported that negative stimuli induced less affect in bilinguals when stimuli were presented in bilinguals’ second, weaker language (L2) than when they were presented in their native language (L1). This effect of L2 use was attributed to increased emotional distance as well as to increased levels of cognitive control during L2 use. Here we investigated how explicit (cognitive reappraisal, i.e. reinterpreting the meaning of the emotional stimulus to alter its emotional impact) and implicit (content labeling, i.e. categorizing the content of the image; and emotion labeling, i.e. naming the emotion induced by the emotional stimulus) emotion regulation strategies are altered in an L2 (English) context in German native speakers with medium to high proficiency in their L2. While previous studies used linguistic stimuli, such as words, to induce affect, here we used images to test whether reduced affect could also be observed for non-linguistic stimuli when presented in an L2 context. We hypothesized that the previously implicated increase in emotional distance and cognitive control in an L2 would result in an L2 advantage in emotion regulation (i.e. leading to less negative emotions compared to an L1 context), by strengthening the effect of linguistic re-evaluation on the evoked emotions. Using a classic emotion regulation paradigm, we examined changes in subjective emotional state ratings during reappraisal, emotion labeling and content labeling in a L1 and L2 context. We found that the strength of evoked affective responses did not depend on the language context in which an image was presented. Crucially, content labeling in L2 was more effective than in L1, whereas emotion labeling did not differ between languages. Overall, evoked responses were regulated most effectively through explicit emotion regulation (reappraisal) in L1 and L2 context. These results demonstrate an L2 advantage effect for emotion regulation through content labeling and suggest that L2 context alters sub-processes implicated in content labeling but not emotion labeling.